Metamorphosis of Sustainable Development Goals 2030: A Shadow of Kafka’s World (IUBAT Review, 2025)
This article critically examines the United Nations' commitment to achieving balanced and integrated sustainable development across economic, social, and environmental dimensions, as outlined in its Sustainable Development Goals (SDGs). Using a qualitative textual analysis grounded in critical theory and discourse analysis it focuses on goals 1, 8, 9, 10, 13, and 17, to uncover the underlying principles of these goals and explores possible inconsistencies, limitations, and deviations. Inspired by the works of German writer Franz Kafka (1883-1924), it investigates how much any contradictory focuses and deviations within the SDGs resemble Kafkaesque scenarios. It uncovers notable parallels between the spirits of the SDGs and Kafka's narratives, highlighting compromises and distortions in the pursuit of sustainable development. It finds that the goals are prone to prioritizing modern economic growth at the expense of addressing socio-economic disparities and mitigating global warming. It concludes that while the SDGs present an ambitious agenda, their internal contradictions undermine their transformative potential.IUBAT Review—A Multidisciplinary Academic Journal, 8(1): 176-190